Analysis of the problems related to traffic and road infrastructure in the area of the Timisoara student complex - Zot Madalina Ileana; Ovidiu-Octavian Maran; Popa Mihaela; Popescu Francisc; Izabel Dungan Luisa (Reciklaža i Održivi Razvoj, 2024)
A common problem in many cities is the continual growth in the number of personal vehicles, which creates numerous challenges and impacts on the environment, the local economy and, most importantly, on the communities and individuals who live and work in these areas. This increase in traffic brings to the forefront issues such as road congestion, air pollution, longer journey times and damage to existing road infrastructure. The aim of this paper is to investigate and analyze the impact of the increase in the number of personal vehicles on traffic and road infrastructure in the student complex of Timisoara. By studying this problem, possible solutions and measures were identified to effectively address these challenges and improve the quality of life of the residents in the area.